(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Wood-ash extracts are used as food additives and medicinals by different ethnic groups in Nigeria. Despite these uses, there is paucity of information on the possible adverse effects on the reproductive health in mammals. This study assessed the toxicity of aqueous wood-ash extract of Parkia biglobosa on reproductive organ in male albino mice. Four different dose levels of wood-ash extract of Parkia biglobosa [0 (control), 5, 50 and 100 mg/kg body weight] were orally administered to 20 mice (5 per group) for seven (7) consecutive days. After 35 days from first day of extract administration, blood samples were collected by retro-orbital phlebotomy and assayed for serum follicle stimulating hormone (FSH), Luteinizing hormone (LH) and testosterone. Mice were sacrificed subsequently by cervical dislocation and testes harvested to examine gonadosomatic index, sperm motility, sperm count, sperm morphology and testicular histopathology using standard methods. ANOVA was used to determine the significant difference among treatments, at P<0.05 level of significance. No significant effect was recorded in testicular weight, FSH, LH and testosterone levels; significant decrease in sperm motility, live/dead sperm and sperm count and increase of abnormal sperm cells were recorded. Frequencies of abnormal sperm cells were significantly higher at 100 mg/kg of the extracts than in control. Dosedependent depletion of spermatogenic cells were recorded in the testes of exposed mice. Aqueous wood ash extract of Parkia biglobosa could have damaging effects on sperms and testicular tissues, which can impair reproduction.